Randomised clinical trial: sodium alginate oral suspension is non‐inferior to omeprazole in the treatment of patients with non‐erosive gastroesophageal disease - Chiu, C.‐T.; Hsu, C.‐M.; Wang, C.‐C.; Chang, J.‐J.; Sung, C.‐M.; Lin, C.‐J.; Chen, L.‐W.; Su, M.‐Y.; Chen, T.‐H. (Alimentary pharmacology & therapeutics, 2013)
Summary Background The burden of gastroesophageal reflux disease (GERD) is increasing in the Asia area and the majority of GERD patients have non‐erosive reflux disease (NERD). Aim To evaluate the efficacy and safety of sodium alginate suspension compared to omeprazole in adult subjects with NERD. Methods In this 4‐week, double‐blind, parallel study, 195 NERD subjects were randomised to one of two treatment groups: sodium alginate suspension 20 mL three times a day and omeprazole 20 mg once daily. The primary efficacy endpoint was the percentage of patients achieving adequate heartburn or regurgitation relief at day 28 assessed by patient diary. The secondary efficacy endpoints included percentage of patients achieving adequate heartburn or regurgitation relief, change from baseline of the Reflux Disease Questionnaire total score at day 14 and 28 from baseline, and patients’ overall satisfaction. Results In this study, 183 subjects were included in the intent‐to‐treat population, and 172 subjects were included in the per‐protocol population. Non‐inferiority of sodium alginate to omeprazole was demonstrated in the intent‐to‐treat population [difference, 2.7% (53.3% vs. 50.5%, P = 0.175), 95% lower confidence interval −11.9%, above the preset margin of −19%]. All of the secondary efficacy endpoints were comparable between two groups. The incidence of adverse event was relatively low and there was no difference between the two groups (5.4% vs. 5.5% for sodium alginate vs. omeprazole). No severe adverse event was noted in this study. Conclusion The study showed that sodium alginate was as effective as omeprazole for symptomatic relief in patients with non‐erosive reflux disease (Clinicaltrials.gov NCT01338077).